Marketing Strategy Universitas Singaperbangsa Karawang - Fajar Ramadhan; Syamsu Yusuf (P4M STIE Putra Bangsa, 2020)
Higher education in Indonesia is a national education subsystem that includes undergraduate, master's, specialist, doctoral, and diploma programs. Higher education institutions are obliged to organize education, research, and community service in accordance with their vision, mission, goals, tasks, and authority. A large number of universities has led to intense competition in getting prospective students. Therefore, universities must have a good